Cuisine, memory and territory in yapatera: culinary heritage and gastronomic tourism in an afro-descendant community - Nole Mendoza, Antonella Yamille (2026)
Cuisine constitutes an intangible cultural heritage; it reflects memory, identity, and everyday practices, and can guide tourism experiences with a strong territorial sense. This qualitative study, with an ethnographic design and descriptive level, was conducted in Yapatera, Piura, with the aim of designing a tourism experience focused on valuing patrimonial cuisine within local gastronomic businesses. In addition, representative recipes were identified and a historical–cultural repertoire was developed to characterize and contextualize these preparations. The population consisted of fourteen managers of local gastronomic businesses, of whom six participated. Criterion-based sampling was used, working with establishments selected for their relevance to understanding the phenomenon and their willingness to participate. Data were collected through a focus group, semi-structured interviews, direct observation, and a literature review, using instruments validated by expert judgment in the fields of tourism and gastronomy. Fieldwork was carried out over two months, with informed consent, the use of field diaries, and audiovisual recording of culinary practices. The results systematize a set of traditional dishes, desserts, and beverages linked to inherited techniques such as sun-drying, slow wood-fired cooking, blanching, and fermentation, as well as to local ingredients including plantain (plátano bellaco), cassava, maize, plum, coconut, and chicha de jora. These preparations are associated with sociocultural contexts of consumption related to patron saint festivities, communal celebrations, family gatherings, and religious practices. Likewise, practices of gastronomic sustainability linked to SDGs 8 and 12 were identified, mainly the promotion of local products, direct purchasing from producers, and the integral use of ingredients. Based on these findings, the experience Patrimonial Flavors of Yapatera: a journey from land to table was designed, structured into a welcome, presentation of ingredients, participatory demonstration, and guided tasting, integrating a starter, main course, dessert, and traditional beverage to responsibly enhance the value of local culinary heritage.